Relation between Change in Subclinical Cerebral and Disease Activity in Paediatric Lupus Nephritis - Noura Ashraf Mahmoud; Sheren Esam Maher; Tamer El Zaeem Esmaeel; Salwa Hussein; Asmaa khalf kamel (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Juvenile-onset systemic lupus erythematosus (JSLE) is a severe autoimmune disease with multi-organ system involvement, with one of its most important complications being lupus nephritis (LN). Complexity in disease pathophysiology, in addition to a lack of sensitive markers, creates difficulty in attaining timely diagnosis and effective therapy. Objective: In this article, an attempt is made to review pathogenesis, clinical presentation, diagnostic criteria, and therapeutic approaches relevant to JSLE and LN, with specific regard for emerging trends in marker development and novel therapeutic approaches. Methods: An in-depth review of current literature regarding JSLE and LN was performed, with a focus placed on disease prevalence, immune deregulation, and multi-visceral disease. In-depth analysis of current diagnostic tests, therapeutic interventions, and future markers has been performed. Results: JSLE is characterized by significant morbidity, with a high prevalence in non-Caucasian populations, early disease onset, and high renal activity. Progress in immunohistochemical techniques has translated into a better prognosis for patients, but timely diagnosis continues to present a challenge. Emerging serum and urinary markers have high potential for use in non-invasive diagnostics. An inter-disciplinary approach in managing concomitant disease and long-term prognosis evaluation is critical. Conclusion: Despite improvements in therapy and diagnostics, additional studies are critical to maximize therapeutic interventions, develop reliable markers, and prevent long-term complications. Patient-focussed and multi-disciplinary care is critical to maximize survival and enhance quality of life in afflicted subjects.